PESAN DAKWAH DALAM “SIPANGNGINGARAN” DI KECAMATAN BARAKA KABUPATEN ENREKANG (Fakultas Dakwah dan Komunikasi, 2020)
This study is a study of the message of Da'wah in Sipangngingaran in Baraka Subdistrict, Enrekang Regency. The main problems raised in this study are how to describe the Sipangngingaran tradition in Baraka District, Enrekang Regency and how the values of da'wah in the Sipangngingaran tradition. This study uses a descriptive method with qualitative research. The research instruments used in data collection were observation, interviews, cameras, recording devices and notebooks. The role of the community as social beings who care about their traditions, where the Sipangngingaran tradition has taught how important it is to remind each other in an activity as a form of caring for each other is leading to a better path and the Sipangngingaran tradition in Baraka District that has Islamic values.